The death of an emperor – Mohammad Reza Shah Pahlavi and his political cancer - Ardavan Khoshnood (Alexandria Journal of Medicine, 2016)
Mohammad Reza Pahlavi, the Shah of Iran, was toppled in the Islamic Revolution of 1979. A year later he passed away from lymphoma, a disease he had secretly battled for several years, but still it remains unknown exactly when he was diagnosed with cancer, if he was aware of his condition and who close to him knew about his illness. Following his 1979 exile from Iran, physicians from numerous countries became involved in his treatment, which was typified by political and medical intrigues, contributing to a suboptimal and dangerous medical care which may ultimately have contributed to his death. After acute surgery of his spleen in June 1980, the Shah’s condition worsened and he eventually passed away on July 27. This study shows that the international intelligence organizations were probably aware of the Shah’s disease, and that the Shah was not cared for in accordance with good medical practice.